Implikasi Hukum dan Politik dalam Pembentukan Danantara sebagai Badan Pengelola Investasi Nasional - Muhammad Yogi Septiyan Priyono; Ariawan Gunadi (Jurnal Hukum Lex Generalis, 2024)
This study aims to analyze the legal and political implications of establishing Danantara as Indonesia’s Sovereign Wealth Fund. The research employs a normative legal method with conceptual and statutory approaches. Danantara’s formation through Law No. 1 of 2025 provides a strong legal basis to consolidate strategic SOE assets for national economic efficiency and growth. However, placing Danantara under direct presidential oversight raises concerns about political interference and weakened independent monitoring. Its superholding status necessitates effective coordination among SOEs to prevent conflicts of interest. From a legal perspective, Danantara demands more adaptive investment regulations to ensure legal certainty for investors. Additionally, the exclusion of oversight by the Audit Board and Anti-Corruption Commission creates risks of power abuse. In conclusion, the government must reinforce independent supervision and ensure fair and transparent regulations so Danantara can operate professionally and accountably.